2018
DOI: 10.1177/1744987117748347
|View full text |Cite
|
Sign up to set email alerts
|

Perception of work-related empowerment of nurse managers

Abstract: The paper aims to analyse the perception of being empowered according to the self-evaluation of nurse managers, presenting it as structural and psychological empowerment. Methods: A questionnaire-based study was conducted. The sample consisted of 193 nurse managers working in a total of seven university and general level hospitals in Lithuania. The Conditions of Work Effectiveness Questionnaire-II measuring structural empowerment and the Work Empowerment Questionnaire measuring psychological empowerment were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
(65 reference statements)
8
17
0
Order By: Relevance
“…A previous review suggested that both career and educational pathways were non‐existent (Dwyer, ). Most FLMs reported having sufficient information to perform well in their work, but some experienced insufficient information from management, politicians and supportive systems, which is consistent with findings from other studies (Trus, Doran, Martinkenas, Asikainen, & Suominen, ). The FLMs reported lacking resources in the form of time, staff and finances, which is also in line with previous research (Hagerman et al, ; Kristiansen et al, ; Udod, Cummings, Care, & Jenkins, ).…”
Section: Discussionsupporting
confidence: 88%
“…A previous review suggested that both career and educational pathways were non‐existent (Dwyer, ). Most FLMs reported having sufficient information to perform well in their work, but some experienced insufficient information from management, politicians and supportive systems, which is consistent with findings from other studies (Trus, Doran, Martinkenas, Asikainen, & Suominen, ). The FLMs reported lacking resources in the form of time, staff and finances, which is also in line with previous research (Hagerman et al, ; Kristiansen et al, ; Udod, Cummings, Care, & Jenkins, ).…”
Section: Discussionsupporting
confidence: 88%
“…6 We consider data literacy to be a research subject located at the intersection of three sets of competences of formula based on the information literacy concept: quantitative reasoning, authentic context, and data/computer science. 7 Kjelvik and Schulthei 8 have assumed that a person who is data-literate (that is to say, able to understand and evaluate information acquired from authentic data, or facts), should have the ability to combine mathematical concepts with the context of an authentic problem that falls within his/her area of expertise and needs. IT skills, as a third component of data literacy, are intended to facilitate the process of analysis and synthesis of data by representing facts in a virtual form.…”
Section: Introductionmentioning
confidence: 99%
“…The unit charge nurses (UCNs) responsible for managing services within the hospital units each play a significant role in creating a positive work environment, ensuring nurses' job satisfaction, maintaining safe and high-quality standards, and developing a PSC (5). It is necessary to develop UCNs' knowledge, attitudes, beliefs, practices, and perceptions about patient safety.…”
Section: Introductionmentioning
confidence: 99%